Illocutionary Speech Acts in The Short Movie “The Translator”: Pragmatic Study - Ayun Widyawanti; Siti Aisyah; Yudy Prasetyo (JELITA, 2024)
Speech acts are a rich category with several pragmatic phenomena that can be studied. The aims of this research are (i) to investigate the types of illocutionary acts and (ii) its functions of illocutionary acts in the short movie “The Translator”. This study used Searle's theory to classified the types of illocutionary act and Leech’s theory to classified the functions of illocutinary. The research method that researchers used was a qualitative descriptive method, because this research seeks to describe data objectively based on the data or facts found. The findings of this study indicated that (i) found 5 types of illocutionary speech acts in inter-player conversations in The Translator short movie, There are 4 assertive illocutionary data, 9 directive data, 13 expressive data, and 1 declarative data, so that the total number of data in the illocutionary type short film “The Translator” is 27 data, (ii) found 4 illocutionary functions in inter-player conversations in The Translator short movie, there are competitive functions is 5 data, convivial is 4 data, collaborative is 1 data and conflictive is 2 data.